The Impact of Job Equivalency Policies and Work Systems on Employee Performance in the Gorontalo City Government: An Information Systems Perspective - Tangguda, Kharisma; Gobel , Lisda Van; Nggilu, Rukiah (Journal of Scientific Insights, 2024)
The purpose of this study was to determine and analyze the influence of job equivalency policy on employee performance, the influence of work system on employee performance and the influence of job equivalency policy and work system simultaneously on employee performance at the Gorontalo City Government. This study used a survey research type with a quantitative approach, a sample of 73 respondents who were employees of the Gorontalo City Government, data analysis using multiple regression analysis with the help of the SPSS version 26 application. The results of the study showed that: (1) partially the job equivalency policy has a negative and significant effect on employee performance. If the job equivalency policy continues to be implemented, employee performance will continue to decline. (2) partially the work system has a positive and significant effect. a good work system continues to be improved, then employee performance will increase. (3) the job equalization policy has a positive and significant effect. the job equalization policy and work system are improved together, then performance will increase. Gorontalo City Government needs to re-evaluate the job equalization policy because it has a negative effect on improving employee performance. Evaluation in terms of human resource management according to competency and competency development through functional training for officials affected by the equalization. There is also a need to be capacity mapping and mapping of human resource needs. In addition, employees in the Gorontalo City Government environment need to continue to improve the work system so that they can improve employee performance.